2024
DOI: 10.2147/ijn.s462917
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Tumor-Targeting Nanobubble with Multiple Scattering Interfaces and its Enhancement of Ultrasound Imaging

Zhengjun Ma,
Yanmei Zhang,
Yupu Zhu
et al.

Abstract: Introduction:Recently, nanobubbles (NBs) have gained significant traction in the field of tumor diagnosis and treatment owing to their distinctive advantages. However, the application of NBs is limited due to their restricted size and singular reflection section, resulting in low ultrasonic reflection. Methods: We synthesized a nano-scale ultrasound contrast agent (IR783-SiO 2 NPs@NB) by encapsulating SiO 2 nanoparticles in an IR783-labeled lipid shell using an improved film hydration method. We characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The study highlights the innovative approach of encapsulating SiO2 nanoparticles in an IR783-labeled lipid shell using an improved film hydration method. 1 This methodology is commendable for addressing the common limitations associated with nanobubbles, particularly their restricted size and singular reflection section, which typically result in low ultrasonic reflection. Larger scattering radii in nanometric UCAs enhance ultrasonic signals, which is previously reported that’s all shared the same structure, with only one contributing interface, 2 with multi-scattering proving more effective, as shown in Zhang’s “rattle”-type SiO 2 NPs.…”
Section: Dear Editormentioning
confidence: 99%
“…The study highlights the innovative approach of encapsulating SiO2 nanoparticles in an IR783-labeled lipid shell using an improved film hydration method. 1 This methodology is commendable for addressing the common limitations associated with nanobubbles, particularly their restricted size and singular reflection section, which typically result in low ultrasonic reflection. Larger scattering radii in nanometric UCAs enhance ultrasonic signals, which is previously reported that’s all shared the same structure, with only one contributing interface, 2 with multi-scattering proving more effective, as shown in Zhang’s “rattle”-type SiO 2 NPs.…”
Section: Dear Editormentioning
confidence: 99%